1997
DOI: 10.1007/bf02490520
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative retention—structure and retention—activity relationship studies of ionic and non-ionic catecholamines by micellar liquid chromatography

Abstract: SummaryWhen ionic surfactants are used as mobile phases in micellar liquid chromatography, MLC, the retention of compounds is governed by hydrophobic and electrostatic forces. In the absence of electrostatic effects, the hydrophobicity of a compound is the predominant factor affecting its retention and its interaction with micelles. Because both interactions should be considered for ionic compounds, a novel retention model is proposed which includes the hydrophobicity of a compound and the molar fraction of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The chromatographic data and the logP values for the series of compounds listed in Table I were collected from the literature in the case of monosubstituted benzenes, aromatic compounds, barbiturates and catecholamines [18,[20][21][22]. Also, a series ofphenylureas and a set formed of seven compounds (named calibration set) was chromatographed under the conditions given in Table I.…”
Section: Datamentioning
confidence: 99%
“…The chromatographic data and the logP values for the series of compounds listed in Table I were collected from the literature in the case of monosubstituted benzenes, aromatic compounds, barbiturates and catecholamines [18,[20][21][22]. Also, a series ofphenylureas and a set formed of seven compounds (named calibration set) was chromatographed under the conditions given in Table I.…”
Section: Datamentioning
confidence: 99%
“…Our research group has demonstrated that the use of retention data obtained in a chromatographic system constituted by polioxyethylene 23 lauryl ether Brij35 micellar mobile phases and C 18 reversed stationary phase in adequate experimental conditions is helpful in describing the biological behaviour of different kinds of drugs (Escuder-Gilabert et al, 1998aCuencaBenito et al, 1998;Sanchis-Mallols et al, 1997;MoleroMonfort et al, 1999MoleroMonfort et al, , 2000Quiñones-Torrelo et al, 1999;Martín-Biosca et al, 1999;Martínez-Pla et al, submitted). We have called this drug biopartitioning simulation chromatographic system biopartitioning micellar chromatography (BMC).…”
Section: Introductionmentioning
confidence: 93%
“…Successful applications of MLC to quantitative retention-activity relationships have been reported to describe substituted phenol bioactivity (Breyer et al,1991), the anesthetic potency of local anesthetics (Escuder-Gilabert et al, 1998a, b), the hypnotic activity of barbiturates (Cuenca-Benito et al, 1998), and the a-and b-adrenergic activity of catecholamines (Sanchis-Mallols et al, 1997). In this paper we have focused our attention on benzodiazepines.…”
Section: Introductionmentioning
confidence: 97%